Synthesis and properties of AFe2O4 (A = Mn, Fe, Co, Ni, Zn)-based nanoparticles coprecipitated from nonaqueous solutions - Yelenich, O. V.; Solopan, S. O.; Tovstolytkin, A. I. (Видавництво Львівської політехніки, 2012)
In this research crystalline ultrafine nanoparticles of AFe2O4 (A = Mn, Fe, Co, Ni, Zn) compounds with spinel structure have been synthesized by the coprecipitation from nonaqueous solutions method. As the nonaqueous medium was used diethylene glycol. The AFe2O4 nanoparticles were characterized using X-Ray diffraction analysis, thermogravimetric analysis, differential thermal analysis, infrared spectroscopy, vibrating sample magnetometry.
Keywords: nonaqueous solution; diethylene glycol; magnetic nanoparticles; coprecipitation